Penggunaan Teknologi Clarifier Tank pada Pengolahan Air Limbah Industri Kelapa Sawit - Muhammad Fikri (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Fikri M. 2021 The use of clarifier tank technology in wastewater treatment of the palm oil industry. In: Herlinda S et al (Eds), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 803-810. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). The palm oil industry has both positive and negative impacts on society and the environment. The positive impact is increasing the country's foreign exchange and public welfare, while the negative impact is creating waste that can pollute the environment if it is not managed properly. This study aimed to purify oil palm wastewater which was generally cloudy in color due to the high content of organic matter. This study used a clarifier tank that is installed after the last pool at the Outlet of the Wastewater Treatment Plant before the wastewater is discharged into the water body. The results were obtained using the clarifier tank technology (settlement tank) by combining the chemical processes (coagulation, flocculation) and physical processes (sedimentation) in one tank unit, which can reduce the total suspended solids (TSS) content in wastewater. The process of purifying wastewater which was originally cloudy in color so that it is safe to be discharged into surface water bodies using several types of chemicals. The types of chemicals used in the precipitation process were soda ash and alum. The soda ash or sodium carbonate served to adjust the pH in the range of 6-7. The alum functioned as a coagulant, namely to agglomerate dirt so that it settled at the bottom of the clarifier tank. The use of clarifier tank technology at the Outlet of the Palm Oil Industry Wastewater Treatment Plant is not only beneficial for humans, but also has a good impact on the surrounding environment, including animals and plants.